Evaluation of pharmacokinetic models for perfusion imaging with dynamic contrast‐enhanced magnetic resonance imaging in porcine skeletal muscle using low‐molecular‐weight contrast agents. Issue 6 (2nd November 2017) - Hindel, Stefan; Papanastasiou, Giorgos; Wust, Peter; Maaß, Marc; Söhner, Anika; Lüdemann, Lutz
Abstract : Purpose: Pharmacokinetic models for perfusion quantification with a low‐molecular‐weight contrast agent (LMCA) in skeletal muscle using dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) were evaluated. Methods: Tissue perfusion was measured in seven regions of interest (ROIs) placed in the total hind leg supplied by the femoral artery in seven female pigs. DCE‐MRI was performed using a 3D gradient echo sequence with k ‐space sharing. The sequence was acquired twice, first after LMCA and then after blood pool contrast agent injection. Blood flow was augmented by continuous infusion of the vasodilator adenosine into the femoral artery, resulting in up to four times increased blood flow. The results obtained with several LMCA models were compared with those of a two‐compartment blood pool model (2CBPM) consisting of a capillary and an arteriolar compartment. Measurements performed with a Doppler flow probe placed at the femoral artery served as ground truth. Results: The two‐compartment exchange model extended by an arteriolar compartment (E2CXM) showed the highest fit quality of all LMCA models and the most significant correlation with the Doppler measurements, r  = 0.78 ( P  < 0.001). The best correspondence between the capillary perfusion measurements of the LMCA models and those of the 2CBPM was found with the E2CXM (slope of the regression line equal to 1, r  = 0.85, P  < 0.001). The results for the clinical patient data corresponded very well with the results obtained in the animal experiments. Conclusions: Double‐contrast agent DCE‐MRI in combination with the E2CXM yields the most reliable results and can be used in clinical routine. Magn Reson Med 79:3154–3162, 2018. © 2017 International Society for Magnetic Resonance in Medicine.